A Bridge over Troubled Water: Managing Parties' Mental Illness in Mediation. Issue 1 (January 2017) - Hickerson, Glen
Abstract : One in five individuals in society has or will have a mental illness at some point in his or her lifetime. Conflict resolution theory, however, largely assumes that all individuals operate within the range of behaviors considered mentally healthy. Evidence suggests that professionals who deal with conflict, however, may have to deal with individuals who have mental health problems more frequently than would be the statistical norm. Clearly then, new theories of practice and norms of mediator behavior are needed to respond to the distinctive challenges presented by engaging with those who face mental health difficulty. This paper surveys the research on how people with mental health challenges approach and respond to conflict and provides practical advice to conflict resolution professionals on how to recognize and tailor their approach to meet the needs of these individuals.